Good wishes as a special genre of oral speech discourse (based on materials of the Kazakh and Chinese languages) (Journal of Oriental Studies, 2017)
In this article will be considered orally-speech genre that plays an important role in the nations culture. In the speakers mind stored certain models of speech behavior, which are recognized as the bearers of this culture the best, correct and necessary. One of the small genres of speech is – good wishes. At the good wishes of the Kazakh and Chinese languages have features that appear in the cognitive consciousness of native speakers. Good wishes will be considered as a special genre of oral speech discourse to determine the level of interpersonal relationships.